Efektivitas Model Pembelajaran Cooperative Learning Tipe Snowball atas Kemampuan Keterampilan Berpikir Kritis terhadap Sekolah Menengah Pertama - Rosfiani, Okta; Zamany, Alfia Zahra; Ismiati, Mely; Sofiyurrahman, Muhammad; Rojaq, Sahid Muhammad (Lembaga Yasin AlSys, 2025)
Modern education demands the development of critical thinking skills as an essential component of the learning process. This study aims to analyze the effectiveness of the Cooperative Learning model of the Snowball Throwing type in enhancing critical thinking skills among junior high school (SMP) students. Employing a qualitative case study approach, data were collected through semi-structured interviews, participatory observations, and document analysis involving teachers and students. The findings indicate that the Snowball Throwing model significantly improves students’ critical thinking abilities, particularly in problem analysis, constructing logical arguments, and objectively evaluating opinions. The activity of throwing questions and engaging in group discussions fosters a collaborative learning environment that encourages active student participation. Key findings include increased social interaction and depth of thinking, effective heterogeneous group division, and challenges such as classroom noise, low confidence among introverted students, and technical difficulties like illegible handwriting. Proposed solutions involve strengthening classroom management, utilizing digital media, and creating a more inclusive learning atmosphere. This study emphasizes the importance of teacher training in classroom management and critical questioning techniques, as well as the need for innovative learning media. The findings support Johnson and Johnson’s (2017) cooperative learning theory and previous research, recommending contextual application of this model alongside the development of mixed-methods approaches for broader generalization.